PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MENJELAJAH KEBERAGAMAN BERBANTUAN PROBLEM BASED LEARNING KELAS IV SD - Muliani Rahayu, Dina; Astuti, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education has an important role in preparing a quality generation. The use of interactive learning media is needed in the teaching and learning process to improve the quality of education. This research aims to develop interactive learning media in the form of comic strips assisted by Problem Based Learning (PBL) for grade IV elementary school students, describe the feasibility of the media, and evaluate its impact on student learning outcomes in Pancasila Education lessons. The method in this study uses Research & Development (R&D) by following the eight steps of Borg and Gall (1981:792). Data were collected through pretest and posttest, observation, interviews, and questionnaires. The results of the study show that the comic entitled "Exploring Diversity" is very feasible to use, with a validation percentage of 88.15% from media experts and 98.75% from material experts. The feasibility of this media is supported by responses from teachers and students on the initial trial, with a percentage of 95% of teachers and 86.25% of students. The impact on learning outcomes can be seen from the N-gain of the initial trial which reached 0.764 (76.4%), showing a high and effective improvement. The N-gain in the usage test also showed a positive result, which was 0.759 (76.03%), which indicates the category of high improvement and effective product. Thus, the PBL- assisted Exploring Diversity comic learning media is effective in increasing student engagement and learning outcomes.